KOMPONEN HASIL JAGUNG MANIS (Zea mays saccharata Sturt) PADA TAILING KECAMATAN TATELU YANG DIBERI PUPUK ORGANIK DAN PUPUK PHONSKA - Sondakh, T. D.; Sumampow, D. M. F.; Polii, M. G. M.; Nangoi, Ronny; Mamarimbing, R.; Titah, Tilda (EUGENIA, 2019)
Tailing is a type of waste produced by mining activities and is characterized by very low physical, chemical, and biological fertility, requiring efforts to amend its quality. The addition of organic materials as a soil ameliorant is one such effort of amendment to enhance success in rehabilitating these degraded areas. The aim of this study is to measure the effects of ameliorant on the growth and yield of sweet corn, determine dosage that will give the best growth and yield, and find out if residual mercury exists in the resultant sweet corn crop. This study used a randomized block design with 6 treatments: A= 40 tons/ha of organic fertilizer; B2= 50 tons/ha of organic fertilizer, C = 60 tons/ha of organic fertilizer, D = 40 tons/ha of organic+ fertilizer, E = 50 tons/ha of organic+ fertilizer, F = 60 ton/ha of organic+ fertilizer. The organic fertilizer used was a mix of 50% water hyacinth + 50% chicken manure, while organic+ fertilizer was a mix of 20% water hyacinth + 20% cow manure + 20% chicken manure + 20% traditional market waste + 20% rice straw. Every treatment was replicated four times, resulting in 24 experimental pots. Variables observed were: 1) cob length, 2) cob diameter, 3) cob weight. Data was analyzed using ANOVA and Tukey’s HSD at a test level of 5%. Results show that organic+ fertilizer increases the yield of sweet corn. A dosage of 60 tons/ha gave the best cobs with a weight of 199,89 grams per cob.